Growth and Nutrients Analysis in Marine Macroalgae - Setthamongkol, Pakawan; Tunkijjanukij, Suriyan; Satapornvanit, Kriengkrai; Salaenoi, Jintana (Agriculture and Natural Resources, 2015)
Macroalgae are one of the most important marine, living, renewable resources and are used for human consumption, animal feed and fertilizer in many countries. Nine species of macroalgae belonging to the Chlorophyta and Rhodophyta divisions—Chaetomorpha crassa, Chaetomorpha linum, Ulva rigida, Caulerpa racemosa, Caulerpa brachypus, Caulerpa lentillifera, Caulerpa taxifolia, Gracilaria tenuistipitata and Gracilaria fisheri—were cultured in a closed system with Guillard’s f/2 medium for 3 wk. After rearing, C. lentillifera achieved the highest mean (± SD) growth rate, followed by U. rigida and C. crassa at 7.28 ± 0.69, 2.66 ± 0.83 and 2.64 ± 0.91 g.d-1, respectively. In addition, C. taxifolia had the highest mean (± SD) protein 33.83 ± 0.21% and lipid 3.26 ± 0.44% contents, and the maximum mean (± SD) carbohydrate 67.84 ± 0.04%, fiber 34.29 ± 0.40% and ash 47.80 ± 0.87% contents were found in U. rigida, C. crassa and C. lentillifera, respectively. Knowledge of the essential compositions in the macroalgae could lead to the potential development of novel seaweed products in the future.